Development of polyvinylidene fluoride-bentonite membrane in membrane distillation system for treatment of palm oil mill effluent - Nor Amirah Safiah, Muhamad (2022)
Clay nanoparticles are commonly incorporated in polymeric membranes to improve the physicochemical properties of the fabricated membrane. However, research on the application of the nanocomposite membrane for industrial effluent treatment remains limited. The aim of this study is to develop polyvinylidene fluoride (PVDF) incorporated bentonite hollow fiber nanocomposite membranes for palm oil mill effluent (POME) treatment using direct contact membrane distillation (DCMD) system. In this work, solutions consisted of 12 wt% PVDF blended with six different bentonite loadings (0.25 wt%, 0.30 wt%, 0.40 wt%, 0.50 wt%, 0.75 wt% and 1.00 wt%) were prepared. The hollow fiber membranes were then fabricated via jet-wet phase inversion method and characterized using scanning electron microscope (SEM) and energy dispersive x-ray (EDX), fourier transform infrared (FTIR), thermal gravimetric analysis (TGA), differential scanning calorimetry (DSC), liquid entry pressure (LEP), membrane porosity, contact angle, X-ray diffraction (XRD) and atomic force microscope (AFM). Prior to testing, the membranes were first tested using deionized water to observe leakage. For the actual application, POME samples collected from an anaerobic pond were used in this study. The highest permeate flux was obtained by PVDF-0.50 wt% bentonite membrane followed by PVDF-0.30 wt% bentonite membrane which was 3.62 ± 1.25 kg/m2.hr and 3.45 ± 0.51 kg/m2.hr respectively during the POME treatment. For removal efficiencies, over 99% of total dissolved solids (TDS), chemical oxygen demand (COD), nitrate nitrogen, color, and turbidity were removed from the effluent. The PVDF-0.30 wt% bentonite membrane performed better than the PVDF-0.50 wt% bentonite membrane in TDS rejection. The PVDF-0.30 wt% bentonite membrane was chosen for further testing with raw POME and long-term studies because the membrane is the most hydrophobic (94.77 ± 0.13°) in comparison to other membranes. During the raw POME test, the permeate flux drops to 1.41 ± 0.62 kg/m2.hr compared to 3.45 ± 0.51 kg/m2.hr when the membrane was tested with POME from an anaerobic pond. The flux reduction can be attributed to the raw POME contains a high concentration of suspended solids, oil and grease which increased the likelihood of fouling problem. To determine the membrane stability and fouling propensity, a long-term DCMD process was conducted for up to 72 hours. It was observed that the permeate flux fluctuated throughout the experiment and then stabilized at the end of the experiment with the average flux is 3.342 ± 1.26 kg/m2.hr. Removal efficiencies of over 95% were reported for all water quality parameters. The results showed that the PVDF-0.30% bentonite membrane could obtain a high permeate flux and produce a high quality permeate that is independent of the fouling during the long-term study. This study highlighted the improvement in membrane properties and performance when bentonite was incorporated into the polymeric membrane.